Maximal ideals in algebras of vector-valued functions - J. W. Kitchen; D. A. Robbins (International Journal of Mathematics and Mathematical Sciences)
Subsuming recent results of the authors [6,7] and J. Arhippainen [l], we investigate further the structure and properties of the maximal ideal spaces of algebras of vector-valued functions.